Pfadabhan̈gigkeit als Forschungsprogramm fur̈ die Agrarok̈onomie - Ludwig Theuvsen (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2004)
– More than a decade ago, path dependence turned out to become a promising research program for agricultural economics. This article reviews important trends in path dependence research and highlights its role in the economics of technology, institutional economics, agricultural economics, and organization theory. Due to potential inefficiencies of path dependent processes, more and more researchers focus on path creation which has as yet not been understood very well. The implications of these recent developments for research questions and methodology of agricultural economics are sketched.
Keywords: 330; Agrarökonomik; Organisationstheorie; Pfadabhängigkeit